42
2007-04-25 08:56:49
·
answer #1
·
answered by floatingbloatedcorpse 4
·
0⤊
0⤋
Take the denominators and find the Least Common Multiple, which in this case is 6........(3*2 = 6, 6*1 = 6, 2*3 = 6)
1/3 + (-1/6) +1/2
Then multiply the fractions by 1 as follows
(2/2)*(1/3) = 2/6
(1/1)*(-1/6) = (-1/6)
(3/3)*(1/2) = 3/6
Since (2/2), (1/1), (3/3) are all equal to 1, you didn't change the value of the fraction, you just changed the numbers. So you're left with:
(2/6) + (-1/6) + (3/6) = (2 - 1 + 3)/6 = 4/6 = 2/3
2007-04-25 15:58:13
·
answer #2
·
answered by Mike 2
·
0⤊
0⤋
I/3 + (-1/6) + (1/2)
= 1/3-1/6+1/2
= 2/6 -1/6 +3/6
= 4/6
=2/3
2007-04-25 15:54:09
·
answer #3
·
answered by ironduke8159 7
·
2⤊
0⤋
1. Get denominators the same number by multiplying 3 by 6 then 6 by 3 and then 2 by 9. The denominators are now all 18.
2. With the 1/3 you have to multiply the numerator by 6 because you have to do the same with the denominator and the numerator. Multiply -1 by 3 and last 1 by 9.
3. The equation is now 6/18-3/18+9/18. You can drop the positive on 1/3 +(-1/6) because there's a negative sign in the ( ).
You don't do any thing to the denominator because they're all the same now. Just work with the numerator.
6-3=3 +9= 12/18 and you could just simplify it. Simplify by dividing the numerator and denominator by 6. 12/6=2 and 18/6=3. The simplified answer is 2/3.
2007-04-25 16:00:44
·
answer #4
·
answered by Al M 2
·
0⤊
0⤋
Need a common denominator to add or subtract fractions. The LCM(2, 3, 6) = 6.
(1/3) = (1/3)(2/2) = 2/6
(1/2) = (1/2)(3/3) = 3/6
Add the numerators and simplify, if possible.
2/6 - 1/6 + 3/6 = 4/6 = 2/3.
2007-04-25 15:56:51
·
answer #5
·
answered by S. B. 6
·
0⤊
0⤋
Find least common denominator
3=1*3
6=1*3*2
2=1*2
LCD = 1*3*2 or 6
1/3 +(-1/6) + (1/2)
=2/6 - 1/6 + 3/6
=3/6 + 3/6
=6/6
=1
2007-04-25 15:58:33
·
answer #6
·
answered by danjlil_43515 4
·
0⤊
0⤋
I/3 + (-1/6) + (1/2) =
mmc (3, 6 e 2) = 6
2/6 - 1/6 + 3/6 = 4/6 or, simplifying: 2/3.
><><
2007-04-25 16:15:11
·
answer #7
·
answered by aeiou 7
·
0⤊
0⤋
To solve this they all need to have the same denominator. So in this case the common denominator is 6.
1/3=2/6
-1/6=-1/6
1/2=3/6
So add (2/6)+(-1/6)+(3/6).
This adds to (4/6) which can be reduced to (2/3)
The answer is 2/3.
2007-04-25 15:56:14
·
answer #8
·
answered by Maestro bestofthebest 2
·
1⤊
0⤋
common demoninater of 6,
so (1x2)/(3x2) -1/6+(1x3)/(2x3)
=4/6
=2/3
2007-04-25 15:51:30
·
answer #9
·
answered by Anonymous
·
1⤊
0⤋